The use of force in humanitarian intervention : morality and practicalities - Janzekovic, John (Ashgate, 2006)
Humanitarian intervention is a many layered and complex concept. This study analyzes the various ethical positions, particularly consequentialism, welfare-utilitarianism and just war theory to unravel this intricate topic and provides a rounded reflection on the lessons learned from the revival of humanitarian intervention as a tool of conflict resolution.